Can “HINTS” aid the Diagnosis of Posterior Circulation Stroke among patients with Acute Vestibular Syndrome? - Sidra Tahir, Nouvaira Tahir, Lubna Meraj, Neelum Zaka, Sadaf Zaman, Kausar Malik, Sidra Tahir, Nouvaira Tahir, Lubna Meraj, Neelum Zaka, Sadaf Zaman, Kausar Malik (Journal of Rawalpindi Medical College, 2022)
Introduction: Identifying posterior circulation stroke in patients with AVS without obvious focal neurological deficits poses a difficult diagnostic challenge. It is estimated that about 10% to 20% of patients who present with acute dizziness to the Emergency department have AVS7. Most AVS patients have a benign peripheral vestibular cause (vestibular neuritis or nonbacterial labyrinthitis), but about 25% have brainstem or cerebellar strokes7, 9-10. Rapid, accurate diagnosis of posterior stroke is important for early management as well as prevention of devastating complications. HINTS is a clinical three-step bedside oculomotor exam, that has been suggested of high diagnostic accuracy in identifying posterior circulation stroke in patients with isolated continuous vertigo. Methods: A comprehensive systematic search of literature was done using the NHS Evidence healthcare databases Medline, EMBASE, CLINIL, Google scholar and Cochrane. Results: 10 relevant articles were identified, combining the results of all six prospective studies showed a total of 338 patients on which Clinical HINTS exam was performed. The overall Hints exam sensitivity was 96.86% 95%CI (92.8-99), specificity 96.09% 95%CI (92.1-98.4) and negative predictive value was 0.03 95%CI (0.01-0.08). ROC analysis was done in which area under curve was found to be 0.965. Conclusion: Delay in diagnosis of posterior stroke can result in 8-fold increase in mortality7. HINTS is a useful clinical bed side oculomotor exam, which if done appropriately by trained ED doctors, could aid in the early recognition of a subtly presenting posterior stroke with “acute isolated continuous vertigo”. Hence, will improve the overall diagnostic evaluation of acute vestibular syndrome.